Epidemiology of Human Fascioliasis and Intestinal Helminthes in Rural Areas of Boyer-Ahmad Township, Southwest Iran; A Population Based Study - HOSSEINI, Ghasem (Iran J Public Health, 2015)
BACKGROUND: Fascioliasis, caused by Fasciola hepatica and F. gigantica, is one of the most important plant and water borne disease in Iran. This study aimed to determine the prevalence of fascioliasis and intestinal helminthes in inhabitants of rural areas of Boyer-Ahmad in Kohgiluyeh and Boyer-Ahmad province in Southwest of Iran. METHODS: Stool samples (1025) were collected from inhabitant of 50 randomly selected villages in Boyer-Ahmad Township. Samples were evaluated with modified Telemann and formalin-ethyl acetate methods. Blood samples of Fasciola positive cases were assessed with ELISA and Western blotting. DNA was extracted from Fasciola eggs from stool of positive individuals and evaluated by molecular (PCR) method and the PCR products were sequenced and analyzed. RESULTS: Of the 1025 participants, 473 (46.1%) were male and 552 (53.9%) were female. The mean age of the subjects was 20.25 (±15.86) years. Fasciola eggs were detected in stools of two cases (0.19%). Blood samples were obtained from the Fasciola positive cases and their infection was further confirmed by ELISA and Western blotting. Molecular analysis revealed that both cases are infected with F. hepatica. Furthermore, seven of participants (0.68%) were found to be infected with H. nana, 4 cases (0.39%) with E. vermicularis, and one case (0.09%) with Trichuris trichiura. CONCLUSION: Findings of this study showed that Boyer-Ahmad district is one of the endemic areas of human fascioliasis in Iran. The study also documented that the rate of helminthic infections in rural areas of the district has drastically declined over the past years.